2019
DOI: 10.1093/gbe/evz196
|View full text |Cite
|
Sign up to set email alerts
|

Corytophanids Replaced the Pleurodont XY System with a New Pair of XY Chromosomes

Abstract: Almost all lizard families in the pleurodont clade share the same XY system. This system was meticulously studied in Anolis carolinensis, where it shows a highly degenerated Y chromosome and a male-specific X chromosome dosage compensation mechanism. Corytophanids (casque-headed lizards) have been proposed as the only family in the pleurodont clade to lack the XY system. In this study, we worked with extensive genomic and transcriptomic data from Basiliscus vittatus, a member of the Corytophanidae family that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
1
20
2
1
Order By: Relevance
“…Of course, we cannot exclude the possibility that some species of skinks do not share the same sex chromosomes. Rare exceptions from the conserved pattern with likely derived sex chromosomes were found in iguanas, anguimorphan lizards and mammals [18,[74][75][76]. However, the current results show that the sex chromosomes homologous to the sandfish are conserved for a long time across most of the phylogenetic diversity of skinks.…”
Section: Towards Resolution Of Controversies On Sex Determination In contrasting
confidence: 66%
“…Of course, we cannot exclude the possibility that some species of skinks do not share the same sex chromosomes. Rare exceptions from the conserved pattern with likely derived sex chromosomes were found in iguanas, anguimorphan lizards and mammals [18,[74][75][76]. However, the current results show that the sex chromosomes homologous to the sandfish are conserved for a long time across most of the phylogenetic diversity of skinks.…”
Section: Towards Resolution Of Controversies On Sex Determination In contrasting
confidence: 66%
“…Even highly differentiated, cytogenetically detectable sex chromosomes can be replaced by poorly differentiated ones, as supported by results in basilisks and Paroedura geckos [130][131][132] (case 10 in figure 2). Ogata et al [66] revealed that the heteromorphic sex chromosome systems probably returned to homomorphy through hybridization in the Japanese wrinkled frog Glandirana rugosa.…”
Section: Is the Sex Chromosome Differentiationmentioning
confidence: 53%
“…2014 ), the green anole A. carolinesis ( Marin et al. 2017 ), casque-headed lizards ( Acosta et al. 2019 ), water skinks ( Cornejo-Paramo et al.…”
Section: Methodsmentioning
confidence: 99%